2021
DOI: 10.20944/preprints202103.0190.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Yield and Cost Effects of Plot Level Wheat Seed Rates and Seed Recycling Practices in the East Gojam Zone, Amhara Region, Ethiopia: Application of the Dose-Response Model

Abstract: Previous studies investigated the effects of seed rates and seed recycling practices on the yield and yield related variables. However, higher yield does not always guarantee cost-efficiency. This study aimed at investigating the yield effects of plot-level seed rate along with the cost-benefit analysis of seed recycling practices. This study has introduced the dose-response model to the existing analytical methods used in analyzing the effect of different agrochemicals on crop yield. A multi-stage stratified … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Utilization of farming extension, researchers and fellow farmers is positively influenced by group participation [48]. Further, Eshete [49] indicated that the farmer-to-farmer extension method, enables farmers to learn from their neighbors and creating a wider access to improved seeds through seed loans and vouchers.…”
Section: Institutional Factorsmentioning
confidence: 99%
“…Utilization of farming extension, researchers and fellow farmers is positively influenced by group participation [48]. Further, Eshete [49] indicated that the farmer-to-farmer extension method, enables farmers to learn from their neighbors and creating a wider access to improved seeds through seed loans and vouchers.…”
Section: Institutional Factorsmentioning
confidence: 99%